1995
DOI: 10.1161/01.hyp.26.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex on Arterial Hemodynamics and Blood Pressure

Abstract: Systolic pressure is lower in premenopausal women than in age-matched men, but underlying alterations are not well characterized. Aging and body size alter arterial function, influencing pressure wave propagation and amplification in peripheral and central arteries. To assess the possibility that systolic pressure differences in women are related to smaller body size, we studied arterial function in 119 men and 104 women. Premenopausal and postmenopausal women were compared with age-matched men. The following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
151
6
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(183 citation statements)
references
References 26 publications
19
151
6
7
Order By: Relevance
“…In addition, some studies have reported that baPWV is strongly influenced by gender in adults and that the difference is due to the beneficial effect of female hormones on arterial stiffness. 26,27 In this study, the baPWV of adolescents was higher in male than in female subjects, and the difference was more evident with increasing age. This finding suggests that the influence of sex hormones contributes to arterial stiffness in postpubertal female adolescents.…”
Section: Discussionmentioning
confidence: 42%
“…In addition, some studies have reported that baPWV is strongly influenced by gender in adults and that the difference is due to the beneficial effect of female hormones on arterial stiffness. 26,27 In this study, the baPWV of adolescents was higher in male than in female subjects, and the difference was more evident with increasing age. This finding suggests that the influence of sex hormones contributes to arterial stiffness in postpubertal female adolescents.…”
Section: Discussionmentioning
confidence: 42%
“…In line with our findings, aortic pulse wave velocity rose with age in both sexes, but the increase was steeper in postmenopausal women than in age-matched men. 14 In premenopausal women greater distensibility of the brachial and femoral arteries partially compensated for the effects of shorter body height and enhanced aortic tapering, but after menopause this compensatory mechanism disappeared. 14 In the present population study, the analyses were adjusted for body mass index, hence for the inverse of body height (squared), but not for aortic tapering.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with a lower average height in women than men. 10 Further support of this concept comes from studies of blood pressure from birth to adulthood 15 and from pooled population studies. 16 Implications Vascular Medicine 2000; 5: [141][142][143][144][145] are further supported by the most recent data from the Framingham Heart Study.…”
Section: Population Studiesmentioning
confidence: 99%
“…If the above mechanism is correct, one would expect to see this more commonly in tall subjects with low aortic pulse wave velocity, and in young adult males rather than young adult females because they are generally taller. 10 One would also expect to see an effect of the phenomenon in population studies.…”
Section: Normal Young Adultsmentioning
confidence: 99%